Analysis of the Effect of Capital, Labor, Raw Materials, and Production on the Income of Ikat Woven Fabric Artisans in Klungkung Regency - Ni Putu Sintyasari; Ni Putu Martini Dewi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to comprehensively analyze the influence of capital, labor, raw materials, and production processes on the income of woven cloth artisans in Klungkung Regency, Bali. The woven cloth industry in this region holds significant historical and cultural value, yet faces challenges in increasing productivity and income. The study employed a quantitative approach with an associative method, combining data collection techniques through direct observation, structured interviews, and secondary data collection from relevant government agencies. The study population consisted of 120 artisan groups, with a sample of 92 groups determined using simple random sampling. Data analysis was conducted using descriptive statistics to map the general conditions of the respondents, and path analysis using SPSS software to identify direct and indirect relationships between variables. The results indicate that capital, labor, and raw materials positively and significantly influence woven cloth production volume. Furthermore, capital, labor, raw materials, and production simultaneously have a significant direct influence on artisan income, with raw materials emerging as the most dominant factor. These findings confirm that the availability of quality raw materials, the quantity and skills of the workforce, and capital adequacy play a central role in improving production performance and artisan welfare. In addition to direct influences, this study also found an indirect effect of capital, labor, and raw materials on income through the mediation of production variables. This suggests that efforts to improve production factors can automatically strengthen income, both directly and through increased production output. The study's recommendations include the need for policies that facilitate access to capital, workforce training, and a sustainable supply of raw materials to support the sustainability of the woven fabric industry as a vital component of the local creative economy and Bali's cultural heritage.